2002
DOI: 10.1002/jez.10167
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of vitellogenin mRNA expression and changes in hemolymph vitellogenin levels during ovarian maturation in the giant freshwater prawn Macrobrachium rosenbergii

Abstract: The dynamics of vitellogenin mRNA expression during ovarian maturation in Macrobrachium rosenbergii were examined by measuring hemolymph vitellogenin (Vg) levels and Vg mRNA expression in the hepatopancreas and ovary at differing reproductive stages in both intact and eyestalk ablated animals. Vg mRNA was quantified using real-time RT-PCR and hemolymph Vg was measured by enzyme immunoassay. In intact animals, Vg mRNA levels in the hepatopancreas and hemolymph Vg levels showed a gradual increase during the molt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
21
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 34 publications
(9 reference statements)
5
21
0
1
Order By: Relevance
“…Dynamic levels of vitellogenin in the haemolymph were observed during reproductive activities. Determination of mRNA expression and vitellogenin levels during ovarian maturation in M. rosenbergii demonstrated a close correlation 24 . A determination of the changes of haemolymph vitellogenin levels could therefore be used to assess the action of the hormone directly 10,11 .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Dynamic levels of vitellogenin in the haemolymph were observed during reproductive activities. Determination of mRNA expression and vitellogenin levels during ovarian maturation in M. rosenbergii demonstrated a close correlation 24 . A determination of the changes of haemolymph vitellogenin levels could therefore be used to assess the action of the hormone directly 10,11 .…”
Section: Introductionmentioning
confidence: 96%
“…The sinus gland extract could reduce the vitellin mRNA expression by over 90% in the Marsupenaeus japonicus ovarian fragments in vitro 20 . Hence the ovarian vitellogenesis stage would be a suitable stage for the determination of the inhibitory effect of VIH because the change in vitellogenin mRNA expression would correlate the change in haemolymph vitellogenin levels as well 24 . In our in vivo assays, the crude eyestalk extract in M-saline at sufficient amounts (equivalent to 1/2 eyestalk) and the acetic methanol eyestalk extract (equivalent to 3 eyestalks) could effectively reduce the haemolymph vitellogenin levels in eye-ablated M. rosenbergii undergoing active ovarian development.…”
Section: Dose Responsementioning
confidence: 99%
“…In recent studies, we examined the effects of eyestalk ablation on patterns of Vg synthesis during the reproductive molt cycle in adult M. rosenbergii (Okumura and Aida, 2001;Jayasankar et al, 2002). The results of these studies showed that eyestalk ablation accelerated Vg synthesis as well as ovarian maturation, but did not alter the overall pattern of Vg expression.…”
mentioning
confidence: 95%
“…The mechanisms by which these hormones regulate molting and gonadal development are complex and have been studied in a number of crustaceans (Fingerman,'87;Chang,'89;Laufer and Landau,'91;Keller,'92;De Kleijn and Van Herp,'98). Removal of the eyestalk deprives the animal of these hormones and affects various physiological processes, including ovarian development and molting (Choy, '87;Zhang et al, '97;Okumura and Aida, 2001;Jayasankar et al, 2002). Eyestalk ablation is commonly employed by aquaculturists to induce rapid ovarian maturation and subsequent spawning in prawns and shrimp in order to overcome the constraint of the unavailability of gravid females.…”
mentioning
confidence: 98%
See 1 more Smart Citation